Modeling the compaction characteristics of fine-grained soils blended with tire-derived aggregates - O'Kelly, Brendan (My University, 2021)
This study aims at modeling the compaction characteristics of fine-grained soils blended with sand-sized (0.075–4.75 mm) recycled tire-derived aggregates (TDAs). Model development and calibration were performed using a large and diverse database of 100 soil–TDA compaction tests (with the TDA-to-soil dry mass ratio ≤ 30%) assembled from the literature. Following a comprehensive statistical analysis, it is demonstrated that the optimum moisture content (OMC) and maximum dry unit weight (MDUW) for soil–TDA blends (across different soil types, TDA particle sizes and compaction energy levels) can be expressed as universal power functions of the OMC and MDUW of the unamended soil, along with the soil to soil–TDA specific gravity ratio. Employing the Bland–Altman analysis, the 95% upper and lower (water content) agreement limits between the predicted and measured OMC values were, respectively, obtained as +1.09% and −1.23%, both of which can be considered negligible for practical applications. For the MDUW predictions, these limits were calculated as +0.67 and −0.71 kN/m3, which (like the OMC) can be deemed acceptable for prediction purposes. Having established the OMC and MDUW of the unamended fine-grained soil, the empirical models proposed in this study offer a practical procedure towards predicting the compaction characteristics of the soil–TDA blends without the hurdles of performing separate laboratory compaction tests, and thus can be employed in practice for preliminary design assessments and/or soil–TDA optimization studies.
PUBLISHED
Part of the Special Issue: "Sustainability in Geotechnics: The Use of Environmentally Friendly Materials"
Keywords: Fine-grained soil; Tire-derived aggregate; Optimum moisture content; Maximum dry unit weight; Bland–Altman analysis; Smart & Sustainable Planet; COMPACTION; Geotechnical Engineering; Geotechnics; MODELING; MODELLING; SOIL; SOIL MODIFICATION; SOIL PARAMETERS; SUSTAINABILITY; Soil Mechanics; Soil Mechanics & Foundations; Waste tires; geotechnical; ground rubber